Environmental-Related Technology on Ecological Footprint: The Case of Germany - Atasever, Gulbahar (International Journal of Energy Economics and Policy, 2025)
In this study, GDP per capita (GDP), non-renewable energy consumption (NREC), renewable energy consumption (REC), and environmental-related technology (ET) on the ecological footprint (EF) were investigated by applying the Autoregressive Distribution Lag Model (ARDL) using time series data from 1990 to 2020 in Germany. According to the results, in the short-run, GDP, NREC and ET increase the EF, while REC decreases the EF. In the long-run, NREC and ET increase the EF, while GDP decreases the EF. Additionally, FMOLS and DOLS robustness tests support the ARDL results. According to these tests, NREC and ET increase the EF in the long-run. DOLS test results also show that REC and GDP will reduce the EF in the long- run. The reason why the increase in environmental technologies in Germany increases the EF is that the number of patents based on environmental technologies can have a positive impact on the environment after reaching a certain level. Accordingly, it is great importance that environmental- related technologies are designed within a framework that supports renewable energy and serves growth that excludes environmental degradation.